Bibliometric analysis of global research in palliative care for cervical cancer - Almobarak, Fhaied (Frontiers in Oncology, 2024)
Objective The present study aims to conduct a comprehensive bibliometric analysis of global research in palliative care for cervical cancer, providing insights into publication trends, authorship patterns, influential journals, and thematic concentrations. Methods A bibliometric analysis approach was employed using metadata extracted from Scopus spanning 2000-2023. The search utilized main terms related to cervical cancer and palliative care. Data analysis and visualization were performed using the Bibliometrix R Package’s web app Biblioshiny and VOSviewer software. Results The study identified 2,492 publications on palliative care for cervical cancer, with a notable peak in 2021. The analysis revealed a diverse publication landscape, encompassing primarily articles. Citation analysis showed a staggering 63,994 citations. The most relevant journals were The Lancet Oncology, Gynecologic Oncology, and International Journal of Gynecological Cancer. The study also highlighted influential authors, institutions, and countries, with Harvard University, the University of Toronto, and the University of Texas MD Anderson Cancer Center leading in publications. Discussion The findings reflected a growing interest in palliative care for cervical cancer, marked by increasing publications over the years. However, the analysis indicated limited international collaborations, with research efforts concentrated in high-income countries. Thematic areas include surgery, palliative care, chemotherapy, radiotherapy, and quality of life. Thus, further collaborations and research in developing countries are needed. Conclusion This bibliometric analysis showcased a comprehensive overview of the global research landscape on palliative care for cervical cancer. The study identified trends, key contributors, and thematic concentrations, offering valuable insights for future research directions and enhancing palliative care services. Addressing the identified gaps, fostering international collaborations, and directing research efforts toward developing countries can contribute to the advancement of palliative care for cervical cancer globally.